PENGARUH PEMBERIAN BERBAGAI DOSIS GLIOKOMPOS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI MERAH (Capsicum annuum L.) - Safuan, La Ode; Rakian, Tresjia C.; Kardiansa, Endi (Jurnal Agroteknos, 2013)
The aim of the research was to study the effect of several glyochompost's dosages on the  growth  and  production of chilli.    The research was carried out in  Lamomea  Village, District Konda, Konawe, Southeast Sulawesi, from December 2012 to February 2013. This research was arranged on  completely randomized block design consisted of 4 treatments, i.e : without glyochompost (Go), glyochompost 30 g (G1), glyochompost 40 g (G2) and glyochompost 50 g (G3) per 20 kg soils. Analysis of variance (ANOVA) was used for statistical data analysis. Duncan's Multiple Range Test (DMRT) was applied to determine the significantly diferent among treatment with   95%   convidence level. The results of the research showed that : (1) glyochompost effectively influenced the plant hight, total productive branch, total numbers and chilli’s weight, (2) Applications of glyochompost 50 gr per 20 kg soils have given the best influence on growth and production of chilli plants. Key words: chilli, growth, glyochompost, plants, production